Liver disease in infancy caused by oxysterol 7α‐hydroxylase deficiency: successful treatment with chenodeoxycholic acid. Issue 5 (22nd March 2014) - Dai, Dongling; Mills, Philippa B.; Footitt, Emma; Gissen, Paul; McClean, Patricia; Stahlschmidt, Jens; Coupry, Isabelle; Lavie, Julie; Mochel, Fanny; Goizet, Cyril; Mizuochi, Tatsuki; Kimura, Akihiko; et al.
Abstract: A child of consanguineous parents of Pakistani origin developed jaundice at 5 weeks and then, at 3 months, irritability, a prolonged prothrombin time, a low albumin, and episodes of hypoglycaemia. Investigation showed an elevated alanine aminotransferase with a normal γ‐glutamyl‐transpeptidase. Analysis of urine by electrospray ionisation tandem mass spectrometry (ESI‐MS/MS) showed that the major peaks were m/z 480 (taurine‐conjugated 3β‐hydroxy‐5‐cholenoic acid) and m/z 453 (sulphated 3β‐hydroxy‐5‐cholenoic acid). Analysis of plasma by gas chromatography‐mass spectrometry (GC‐MS) showed increased concentrations of 3β‐hydroxy‐5‐cholenoic acid, 3β‐hydroxy‐5‐cholestenoic acid and 27‐hydroxycholesterol, indicating oxysterol 7α‐hydroxylase deficiency. The patient was homozygous for a mutation (c.1249C>T) in CYP7B1 that alters a highly conserved residue in oxysterol 7α‐hydroxylase (p.R417C) – previously reported in a family with hereditary spastic paraplegia type 5. On treatment with ursodeoxycholic acid (UDCA), his condition was worsening, but on chenodeoxycholic acid (CDCA), 15 mg/kg/d, he improved rapidly. A biopsy (after 2 weeks on CDCA), showed a giant cell hepatitis, an evolving micronodular cirrhosis, and steatosis. The improvement in liver function on CDCA was associated with a drop in the plasma concentrations and urinary excretions of the 3β‐hydroxy‐Δ 5 bile acids which are considered hepatotoxic. At age 5 years (on CDCA, 6 mg/kg/d), he was thriving with normal liver function. Neurological development was normal apart from a tendency to trip. Examination revealed pes cavus but no upper motor neuron signs. The findings in this case suggest that CDCA can reduce the activity of cholesterol 27‐hydroxylase – the first step in the acidic pathway for bile acid synthesis.